A boiling water resistant flame retardant starch-based wood adhesive and its preparation method and application
Through the enzyme-catalyzed hydrolysis and hyperbranched cross-linking network strategy, combined with DIHP and nanohybrid DE@TA, the shortcomings of starch-based adhesives in boiling water resistance and flame retardant properties are solved, and high-performance adhesives are achieved.
Patent Information
- Application Number
- CN202411789526.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-06
AI Technical Summary
The existing starch-based adhesives have shortcomings in their boiling water resistance and flame retardant properties, and traditional oxidants have problems such as high cost, high pollution, strong irritation and long reaction time.
Starch hydrolysate is generated by enzyme-catalyzed hydrolysis reaction and mixed with DIHP aqueous solution and nanohybrid DE@TA to build a hyperbranched crosslinking network structure to improve the boiling water resistance and flame retardant properties of the adhesive.
It significantly improves the boiling water resistance and flame retardant properties of the adhesive, and has excellent bonding strength in boiling water, with an oxygen index of 32.1%, meeting the standards of B1 flame retardant materials.
Smart Images

Figure CN119432255B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of starch-based adhesive materials, and in particular to a boiling water-resistant flame-retardant starch-based wood adhesive and a preparation method and application thereof. Background Art
[0002] In the wood processing and furniture manufacturing industries, adhesives are indispensable materials for connecting and fixing wood components. Traditional wood adhesives, such as phenolic resin (PF), urea-formaldehyde resin (UF) and melamine formaldehyde resin (MF), are mainly made from non-renewable petroleum resources. These synthetic adhesives may not only release harmful volatile organic compounds (VOCs) during production and use, but some of their components are even carcinogenic, posing a serious threat to air quality and human health. Therefore, the development of environmentally friendly and renewable biomass adhesives has become a research hotspot.
[0003] As an abundant natural polymer material, starch is considered to be an ideal raw material for the preparation of environmentally friendly adhesives due to its renewable, low cost and good biodegradability. However, unmodified starch-based adhesives have the problems of low wet bonding strength and poor waterproof performance, which limits their application in the field of wood adhesives. In order to improve these properties, a variety of chemical, physical and biological modification methods have been tried, such as oxidation, cross-linking, esterification and graft copolymerization, to improve the performance of starch-based adhesives.
[0004] Despite this, existing starch-based adhesives still face challenges in terms of boiling water resistance and flame retardancy. Traditional oxidants such as NaIO4 and KMnO4 have disadvantages such as high cost, high pollution, strong irritation and long reaction time in the oxidative modification of starch. In addition, the improvement of flame retardancy often requires the addition of additional flame retardants, which may affect other properties of the adhesive, such as bonding strength and environmental friendliness. Therefore, how to improve the boiling water resistance and flame retardancy of adhesives without affecting the bonding performance of the adhesive has become a problem that technicians in this field need to solve urgently. Summary of the invention
[0005] In view of this, the present invention provides a boiling water resistant flame retardant starch-based wood adhesive and a preparation method and application thereof, the purpose of which is to solve the technical problems that existing adhesives cannot take into account bonding performance, boiling water resistance and flame retardant properties.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] The present invention provides a method for preparing a boiling water resistant flame retardant starch-based wood adhesive, comprising the following steps:
[0008] S1, mixing starch, water and α-amylase and performing a hydrolysis reaction to obtain a starch hydrolysate;
[0009] S2, mixing the starch hydrolysate and the DIHP aqueous solution and reacting them to obtain an S-DIHP material;
[0010] S3, mixing the nano-hybrid DE@TA and S-DIHP materials to obtain a boiling water resistant flame retardant starch-based wood adhesive;
[0011] In step S2, the method for preparing the DIHP aqueous solution comprises the following steps:
[0012] (a) mixing 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, maleic anhydride and tetrahydrofuran and reacting them to obtain a reaction product a;
[0013] (b) mixing the reaction product a and triethylenetetramine and reacting them to obtain a reaction product b;
[0014] (c) mixing the reaction product b with ethylenediamine and reacting them to obtain a reaction product c;
[0015] (d) mixing the reaction product c with water to obtain a DIHP aqueous solution;
[0016] In step S3, the preparation method of the nanohybrid DE@TA comprises the following steps:
[0017] (1) mixing 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, coupling agent KH560 and toluene and reacting them to obtain a reaction product d;
[0018] (2) mixing the reaction product d, ethanol and water and reacting them to obtain polysiloxane;
[0019] (3) The nanohybrid DE@TA is obtained by mixing polysiloxane, tannic acid and water.
[0020] Furthermore, in step S1, the mass ratio of starch, water and α-amylase is 1-5:5-15:0.05-1;
[0021] The temperature of the hydrolysis reaction is 80-100° C., and the time of the hydrolysis reaction is 10-15 hours.
[0022] Furthermore, in step S2, the mass ratio of the starch hydrolysate to the DIHP aqueous solution is 1:1-3;
[0023] The reaction temperature is 70-90° C., and the reaction time is 0.5-3 h.
[0024] Further, in the step S2, in the process of preparing the DIHP aqueous solution, in step (a), the amount ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, maleic anhydride and tetrahydrofuran is 50-60 g: 20-30 g: 40-60 mL; the reaction temperature is 50-70° C., and the reaction time is 10-15 h;
[0025] In step (b), the reaction temperature is 70-90° C., the reaction time is 0.5-2 h; the amount ratio of triethylenetetramine to tetrahydrofuran is 5-15 g:40-60 mL;
[0026] In step (c), the reaction temperature is 90-110° C., the reaction time is 1-3 h; the amount ratio of ethylenediamine to tetrahydrofuran is 20-30 g: 40-60 mL;
[0027] In step (d), the usage ratio of water to tetrahydrofuran is 100-120 g:40-60 mL.
[0028] Furthermore, in step S3, the mass ratio of the nano-hybrid DE@TA and the S-DIHP material is 10-20:100.
[0029] Furthermore, in the step S3, in the process of preparing the nanohybrid DE@TA, in step (1), the mass ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, coupling agent KH560 and toluene is 5-15:5-15:20-40; the reaction temperature is 90-110° C., and the reaction time is 4-8 hours;
[0030] In step (2), the reaction temperature is 50-70° C., the reaction time is 4-8 hours; the mass ratio of ethanol, water and toluene is 20-30:1-5:20-40;
[0031] In step (3), the mass ratio of polysiloxane, tannic acid and water is 1-5:1-5:40-60.
[0032] The invention provides a boiling water resistant flame retardant starch-based wood adhesive prepared by the preparation method.
[0033] The present invention also provides the use of the above-mentioned boiling water resistant flame retardant starch-based wood adhesive in the preparation of laminated plywood, which is characterized by comprising the following steps:
[0034] The poplar veneer is dried, glued, assembled and hot-pressed in sequence to obtain a laminated plywood;
[0035] In the gluing process, the amount of the boiling water resistant flame retardant starch-based wood adhesive on the poplar veneer is 200-400 g / m 2;
[0036] The temperature of the hot pressing is 170-190° C., the pressure of the hot pressing is 0.5-2 MPa, and the time of the hot pressing is 3-10 min.
[0037] Furthermore, after the drying, the moisture content of the poplar veneer is ≤8%.
[0038] It can be seen from the above technical solution that compared with the prior art, the beneficial effects of the present invention are as follows:
[0039] (1) Enhanced boiling water resistance: Through the hyperbranched cross-linking network strategy, a dense covalent network structure was constructed, which enhanced the waterproof performance of the adhesive and significantly improved its bonding strength in boiling water.
[0040] (2) Significant improvement in flame retardancy: The introduction of phosphorus-containing hyperbranched polyamine and silicon-containing tannin core-shell structure improves the flame retardancy of the adhesive. This structure can form a carbon layer during the combustion process, effectively preventing the transfer of oxygen and heat, thereby achieving a flame retardant effect. The oxygen index of the prepared adhesive reached 32.1%, meeting the standard of B1 flame retardant materials, providing a new solution for the fire safety of wood adhesives.
[0041] (3) Improvement of comprehensive performance: The enzyme-catalyzed hydrolysis strategy improves the hydrolysis efficiency of starch, thereby obtaining a higher performance adhesive. The addition of the core-shell structured nanohybrid DE@TA not only improves the bonding performance of the adhesive, but also enhances its mechanical strength and thermal stability.
[0042] (4) Innovative synthesis strategy: By combining enzyme-catalyzed hydrolysis and hyperbranched cross-linking network strategy, an innovative synthesis method of starch-based adhesives was developed, providing new ideas for the development of high-performance adhesives.
[0043] In summary, this new boiling water resistant flame retardant starch-based wood adhesive has significant improvements over existing technologies in terms of environmental protection, boiling water resistance, flame retardancy, comprehensive performance and cost-effectiveness, providing the wood processing industry with a safer, more environmentally friendly and higher-performance adhesive option. BRIEF DESCRIPTION OF THE DRAWINGS
[0044] Figure 1 Schematic diagram of the synthesis of S-DIHP material;
[0045] Figure 2 Schematic diagram of the synthesis of nanohybrid DE@TA;
[0046] Figure 3 Schematic diagram of the synthesis of boiling water resistant flame retardant starch-based wood adhesive. DETAILED DESCRIPTION
[0047] The present invention provides a method for preparing a boiling water resistant flame retardant starch-based wood adhesive, comprising the following steps:
[0048] S1, mixing starch, water and α-amylase and performing a hydrolysis reaction to obtain a starch hydrolysate;
[0049] S2, mixing the starch hydrolysate and the DIHP aqueous solution and reacting them to obtain an S-DIHP material;
[0050] S3, mixing the nano-hybrid DE@TA and S-DIHP materials to obtain a boiling water resistant flame retardant starch-based wood adhesive;
[0051] In step S2, the method for preparing the DIHP aqueous solution comprises the following steps:
[0052] (a) mixing 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, maleic anhydride and tetrahydrofuran and reacting them to obtain a reaction product a;
[0053] (b) mixing the reaction product a and triethylenetetramine and reacting them to obtain a reaction product b;
[0054] (c) mixing the reaction product b with ethylenediamine and reacting them to obtain a reaction product c;
[0055] (d) mixing the reaction product c with water to obtain a DIHP aqueous solution;
[0056] In step S3, the preparation method of the nanohybrid DE@TA comprises the following steps:
[0057] (1) mixing 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, coupling agent KH560 and toluene and reacting them to obtain a reaction product;
[0058] (2) mixing the reaction product, ethanol and water and reacting them to obtain polysiloxane;
[0059] (3) The nanohybrid DE@TA is obtained by mixing polysiloxane, tannic acid and water.
[0060] In the present invention, in step S1, the mass ratio of starch, water and α-amylase is 1-5: 5-15: 0.05-1, preferably 2-4: 7-12: 0.075-0.6, and more preferably 3: 10: 0.15-0.3;
[0061] The temperature of the hydrolysis reaction is 80-100° C., preferably 85-95° C., and more preferably 90° C.; the time of the hydrolysis reaction is 10-15 h, preferably 11-14 h, and more preferably 12-13 h.
[0062] In the present invention, in step S2, the mass ratio of the starch hydrolysate to the DIHP aqueous solution is 1:1-3, preferably 1:1.5-2.5, and more preferably 1:2;
[0063] The reaction temperature is 70-90° C., preferably 75-85° C., and more preferably 80° C.; the reaction time is 0.5-3 h, preferably 1-2 h, and more preferably 1.5 h.
[0064] In the present invention, in the step S2, in the process of preparing the DIHP aqueous solution, in step (a), the amount ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, maleic anhydride and tetrahydrofuran is 50-60g:20-30g:40-60mL, preferably 52-58g:22-28g:45-55mL, and more preferably 54-56g:24-26g:50mL; the reaction temperature is 50-70°C, preferably 55-65°C, and more preferably 60°C; the reaction time is 10-15h, preferably 11-14h, and more preferably 12-13h; the reaction is carried out in a protective gas, and the protective gas is preferably nitrogen;
[0065] In step (b), the reaction temperature is 70-90° C., preferably 75-85° C., and more preferably 80° C.; the reaction time is 0.5-2 h, and preferably 1-1.5 h; the amount ratio of triethylenetetramine to tetrahydrofuran is 5-15 g:40-60 mL, preferably 8-12 g:45-55 mL, and more preferably 10 g:50 mL; the reaction is carried out in a protective gas, and the protective gas is preferably nitrogen;
[0066] In step (c), the reaction temperature is 90-110° C., preferably 95-105° C., and more preferably 100° C.; the reaction time is 1-3 h, preferably 1.5-2.5 h, and more preferably 2 h; the amount ratio of ethylenediamine to tetrahydrofuran is 20-30 g:40-60 mL, preferably 22-28 g:45-55 mL, and more preferably 24-26 g:50 mL;
[0067] In step (d), the usage ratio of water to tetrahydrofuran is 100-120 g:40-60 mL, preferably 105-115 g:45-55 mL, and more preferably 110 g:50 mL.
[0068] In the present invention, in step S3, the mass ratio of the nano-hybrid DE@TA to the S-DIHP material is 10-20:100, preferably 12-18:100, and more preferably 14-16:100.
[0069] In the present invention, in the step S3, in the process of preparing the nano hybrid DE@TA, in step (1), the mass ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, coupling agent KH560 and toluene is 5-15:5-15:20-40, preferably 8-12:8-12:25-35, and more preferably 10:10:30; the reaction temperature is 90-110°C, preferably 95-105°C, and more preferably 100°C; the reaction time is 4-8h, preferably 5-7h, and more preferably 6h; the reaction is carried out in a protective gas, and the protective gas is preferably nitrogen;
[0070] In step (2), the reaction temperature is 50-70°C, preferably 55-65°C, and more preferably 60°C; the reaction time is 4-8h, preferably 5-7h, and more preferably 6h; the mass ratio of ethanol, water, and toluene is 20-30:1-5:20-40, preferably 22-28:2-4:25-35, and more preferably 24-26:3:30; the reaction is carried out in a protective gas, and the protective gas is preferably nitrogen;
[0071] In step (3), the mass ratio of polysiloxane, tannic acid and water is 1-5:1-5:40-60, preferably 2-4:2-4:45-55, and more preferably 3:3:50.
[0072] The invention provides a boiling water resistant flame retardant starch-based wood adhesive prepared by the preparation method.
[0073] The present invention also provides the use of the above-mentioned boiling water resistant flame retardant starch-based wood adhesive in the preparation of laminated plywood, characterized in that it comprises the following steps:
[0074] The poplar veneer is dried, glued, assembled and hot-pressed in sequence to obtain a laminated plywood;
[0075] In the gluing process, the amount of the boiling water resistant flame retardant starch-based wood adhesive on the poplar veneer is 200-400 g / m 2 , preferably 250 to 350 g / m 2 , more preferably 300g / m 2 ;
[0076] The hot pressing temperature is 170-190°C, preferably 175-185°C, and more preferably 180°C; the hot pressing pressure is 0.5-2MPa, preferably 1-1.5MPa; the hot pressing time is 3-10min, preferably 4-8min, and more preferably 5-6min.
[0077] In the present invention, after the drying, the moisture content of the poplar veneer is ≤8%, preferably ≤6%, and more preferably ≤5%.
[0078] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0079] Example 1
[0080] Preparation of DIHP aqueous solution:
[0081] At room temperature, 54 g of 9,10-dihydro-9-oxo-10-phosphaphenanthrene-10-oxide (DOPO) and 28 g of maleic anhydride (ITA) were weighed and mixed into a clean reaction bottle, and 50 mL of tetrahydrofuran was added and stirred. After mixing evenly, the reaction bottle was stirred continuously in a reaction pot at 60°C under nitrogen protection for 12 hours. After the reaction was completed, the tetrahydrofuran was recovered by rotary evaporation.
[0082] 9.5 g of triethylenetetramine was added to the above reaction bottle, and then placed in a reactor at 80° C. for 1 h. After the reaction was completed, 25.8 g of ethylenediamine was added to the reaction bottle and dehydrated for 2 h under solvent-free conditions at a reaction temperature of 100° C. The product obtained after the reaction was mixed with 112.8 g of deionized water to prepare a DIHP aqueous solution.
[0083] Preparation of Nanohybrid DE@TA:
[0084] First, in a clean reaction bottle, 10.8 g DOPO and 11.8 g KH560 were dissolved in 30 g toluene solution. Then, under nitrogen protection, the reaction was carried out in a reaction pot at 100°C for 6 h. After the reaction was completed, the toluene solvent was recovered by rotary evaporation to obtain the reaction product.
[0085] 27 g of ethanol and 3 g of deionized water were added to the reaction bottle containing the reaction product, mixed evenly, and reacted in a reaction pot at 60° C. for 6 h. After the reaction was completed, the ethanol and water were removed by rotary evaporation to obtain polysiloxane (DE).
[0086] Add 2 g of tannic acid (TA), 50 g of deionized water and 2 g of DE into a clean beaker, mix well and stir at room temperature for 12 h to finally obtain the nanohybrid DE@TA.
[0087] Preparation of boiling water resistant flame retardant starch-based wood adhesive:
[0088] 2 g of starch was weighed at room temperature, dispersed in 10 g of deionized water, mixed with 0.3 g of α-amylase, placed in a reaction pot at 90° C., and stirred continuously for 12 h to obtain a starch hydrolyzate.
[0089] 6 g of the DIHP aqueous solution prepared above was weighed and added to 3 g of starch hydrolysate, and reacted at 90° C. for 3 h. After the reaction was completed, deionized water was added according to its solid content of 50% to completely dissolve it to obtain S-DIHP material.
[0090] The nano-hybrid DE@TA was added into the S-DIHP material at a mass ratio of 10%, and the mixture was evenly mixed to obtain a boiling water resistant flame retardant starch-based wood adhesive (S-DIHP-DE@TA adhesive).
[0091] Example 2
[0092] Preparation of DIHP aqueous solution:
[0093] At room temperature, 54 g of 9,10-dihydro-9-oxo-10-phosphaphenanthrene-10-oxide (DOPO) and 28 g of maleic anhydride (ITA) were weighed and mixed into a clean reaction bottle, and 50 mL of tetrahydrofuran was added and stirred. After mixing evenly, the reaction bottle was stirred continuously in a reaction pot at 60°C under nitrogen protection for 12 hours. After the reaction was completed, the tetrahydrofuran was recovered by rotary evaporation.
[0094] 9.5 g of triethylenetetramine was added to the above reaction bottle, and then placed in a reactor at 80° C. for 1 h. After the reaction was completed, 25.8 g of ethylenediamine was added to the reaction bottle and dehydrated for 2 h under solvent-free conditions at a reaction temperature of 100° C. The product obtained after the reaction was mixed with 112.8 g of deionized water to prepare a DIHP aqueous solution.
[0095] Preparation of Nanohybrid DE@TA:
[0096] First, in a clean reaction bottle, 10.8 g DOPO and 11.8 g KH560 were dissolved in 30 g toluene solution. Then, under nitrogen protection, the reaction was carried out in a reaction pot at 100°C for 6 h. After the reaction was completed, the toluene solvent was recovered by rotary evaporation to obtain the reaction product.
[0097] 27 g of ethanol and 3 g of deionized water were added to the reaction bottle containing the reaction product, mixed evenly, and reacted in a reaction pot at 60° C. for 6 h. After the reaction was completed, the ethanol and water were removed by rotary evaporation to obtain polysiloxane (DE).
[0098] Add 2 g of tannic acid (TA), 50 g of deionized water and 2 g of DE into a clean beaker, mix well and stir at room temperature for 12 h to finally obtain the nanohybrid DE@TA.
[0099] Preparation of boiling water resistant flame retardant starch-based wood adhesive:
[0100] 2 g of starch was weighed at room temperature, dispersed in 10 g of deionized water, mixed with 0.3 g of α-amylase, placed in a reaction pot at 90° C., and stirred continuously for 12 h to obtain a starch hydrolyzate.
[0101] 6 g of the DIHP aqueous solution prepared above was weighed and added to 3 g of starch hydrolysate, and reacted at 90° C. for 3 h. After the reaction was completed, deionized water was added according to its solid content of 50% to completely dissolve it to obtain S-DIHP material.
[0102] The nano-hybrid DE@TA is added into the S-DIHP material at a mass ratio of 15%, and the mixture is evenly mixed to obtain a boiling water resistant flame retardant starch-based wood adhesive (S-DIHP-DE@TA adhesive).
[0103] Example 3
[0104] Preparation of DIHP aqueous solution:
[0105] At room temperature, 54 g of 9,10-dihydro-9-oxo-10-phosphaphenanthrene-10-oxide (DOPO) and 28 g of maleic anhydride (ITA) were weighed and mixed into a clean reaction bottle, and 50 mL of tetrahydrofuran was added and stirred. After mixing evenly, the reaction bottle was stirred continuously in a reaction pot at 60°C under nitrogen protection for 12 hours. After the reaction was completed, the tetrahydrofuran was recovered by rotary evaporation.
[0106] 9.5 g of triethylenetetramine was added to the above reaction bottle, and then placed in a reactor at 80° C. for 1 h. After the reaction was completed, 25.8 g of ethylenediamine was added to the reaction bottle and dehydrated for 2 h under solvent-free conditions at a reaction temperature of 100° C. The product obtained after the reaction was mixed with 112.8 g of deionized water to prepare a DIHP aqueous solution.
[0107] Preparation of Nanohybrid DE@TA:
[0108] First, in a clean reaction bottle, 10.8 g DOPO and 11.8 g KH560 were dissolved in 30 g toluene solution. Then, under nitrogen protection, the reaction was carried out in a reaction pot at 100°C for 6 h. After the reaction was completed, the toluene solvent was recovered by rotary evaporation to obtain the reaction product.
[0109] 27 g of ethanol and 3 g of deionized water were added to the reaction bottle containing the reaction product, mixed evenly, and reacted in a reaction pot at 60° C. for 6 h. After the reaction was completed, the ethanol and water were removed by rotary evaporation to obtain polysiloxane (DE).
[0110] Add 2 g of tannic acid (TA), 50 g of deionized water and 2 g of DE into a clean beaker, mix well and stir at room temperature for 12 h to finally obtain the nanohybrid DE@TA.
[0111] Preparation of boiling water resistant flame retardant starch-based wood adhesive:
[0112] 2 g of starch was weighed at room temperature, dispersed in 10 g of deionized water, mixed with 0.3 g of α-amylase, placed in a reaction pot at 90° C., and stirred continuously for 12 h to obtain a starch hydrolyzate.
[0113] 6 g of the DIHP aqueous solution prepared above was weighed and added to 3 g of starch hydrolysate, and reacted at 90° C. for 3 h. After the reaction was completed, deionized water was added according to its solid content of 50% to completely dissolve it to obtain S-DIHP material.
[0114] The nano hybrid DE@TA is added into the S-DIHP material at a mass ratio of 20%, and the mixture is evenly mixed to obtain a boiling water resistant flame retardant starch-based wood adhesive (S-DIHP-DE@TA adhesive).
[0115] Comparative Example 1
[0116] Preparation of DIHP aqueous solution:
[0117] At room temperature, 54 g of 9,10-dihydro-9-oxo-10-phosphaphenanthrene-10-oxide (DOPO) and 28 g of maleic anhydride (ITA) were weighed and mixed into a clean reaction bottle, and 50 mL of tetrahydrofuran was added and stirred. After mixing evenly, the reaction bottle was stirred continuously in a reaction pot at 60°C under nitrogen protection for 12 hours. After the reaction was completed, the tetrahydrofuran was recovered by rotary evaporation.
[0118] 9.5 g of triethylenetetramine was added to the above reaction bottle, and then placed in a reactor at 80° C. for 1 h. After the reaction was completed, 25.8 g of ethylenediamine was added to the reaction bottle and dehydrated for 2 h under solvent-free conditions at a reaction temperature of 100° C. The product obtained after the reaction was mixed with 112.8 g of deionized water to prepare a DIHP aqueous solution.
[0119] 2 g of starch was weighed at room temperature, dispersed in 10 g of deionized water, mixed with 0.3 g of α-amylase, placed in a reaction pot at 90° C., and stirred continuously for 12 h to obtain a starch hydrolyzate.
[0120] 6 g of the DIHP aqueous solution prepared above was weighed and added to 3 g of starch hydrolysate, and reacted at 70° C. for 3 h. After the reaction was completed, deionized water was added according to its solid content of 50% to completely dissolve it to obtain S-DIHP material, which was named S-DIHP adhesive.
[0121] Application Example 1
[0122] (1) Drying: Poplar veneer is dried until the moisture content is less than 8%;
[0123] (2) Gluing: The adhesive prepared in Example 1 was applied to both sides of the dried poplar veneer, with a total coating amount of 300 g / m 2 ; No need to wait for it to dry after painting;
[0124] (3) Assembling the blanks: Arranging and assembling the poplar veneers coated with adhesive materials in a vertical grain pattern to form blanks of a predetermined shape and size;
[0125] (4) Hot pressing: The assembled product is placed in a hot press for pressing at a temperature of 180°C, a pressure of 1.0 MPa, and a time of 6 min to obtain a laminated plywood.
[0126] Application Example 2
[0127] The same as Application Example 1, except that the adhesive used is prepared in Example 2.
[0128] Application Example 3
[0129] The same as Application Example 1, except that the adhesive used is prepared in Example 3.
[0130] Application Example 4
[0131] The same as Application Example 1, except that the adhesive used is prepared in Comparative Example 1.
[0132] Performance Testing
[0133] The evaluation of bonding strength was carried out in accordance with the provisions of the national standard GB / T17657-2013. First, the laminated plywood samples were cut into the same size (100mm×25mm) and then slotted so that the area of the bonding part was 25mm×25mm. Next, the laminated plywood samples were immersed in a water bath at 63±3℃ and 93±3℃ for 3 hours, respectively. After being taken out, they were placed at room temperature for 10 minutes, and then the bonding strength was tested using an electronic universal mechanical testing machine. The test results are shown in Table 1.
[0134] Table 1 Properties of laminated plywood prepared with different adhesives
[0135]
[0136] As can be seen from Table 1, the dry shear strength of the adhesives prepared by the present invention is not much different. However, in hot water or boiling water, the bonding performance of the adhesive with the nano-hybrid DE@TA added is significantly better than that of the adhesive without the nano-hybrid DE@TA added.
[0137] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a boiling water resistant flame retardant starch-based wood adhesive, characterized in that: The following steps are involved: S1, mixing starch, water and α-amylase and performing a hydrolysis reaction to obtain a starch hydrolysate; S2, mixing the starch hydrolysate and the DIHP aqueous solution and reacting them to obtain an S-DIHP material; S3, mixing the nano-hybrid DE@TA and S-DIHP materials to obtain a boiling water resistant flame retardant starch-based wood adhesive; In step S2, the method for preparing the DIHP aqueous solution comprises the following steps: (a) mixing 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, maleic anhydride and tetrahydrofuran and reacting them to obtain a reaction product a; (b) mixing the reaction product a and triethylenetetramine and reacting them to obtain a reaction product b; (c) mixing the reaction product b with ethylenediamine and reacting them to obtain a reaction product c; (d) mixing the reaction product c with water to obtain a DIHP aqueous solution; In step S3, the preparation method of the nanohybrid DE@TA comprises the following steps: (1) mixing 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, coupling agent KH560 and toluene and reacting them to obtain a reaction product d; (2) mixing the reaction product d, ethanol and water and reacting them to obtain polysiloxane; (3) The nanohybrid DE@TA is obtained by mixing polysiloxane, tannic acid and water.
2. The preparation method according to claim 1, characterized in that: In step S1, the mass ratio of starch, water and α-amylase is 1-5:5-15:0.05-1; The temperature of the hydrolysis reaction is 80-100° C., and the time of the hydrolysis reaction is 10-15 hours.
3. The preparation method according to claim 2, characterized in that: In the step S2, the mass ratio of the starch hydrolysate to the DIHP aqueous solution is 1:1-3; The reaction temperature is 70-90° C., and the reaction time is 0.5-3 h.
4. The preparation method according to claim 1, characterized in that: In the step S2, in the process of preparing the DIHP aqueous solution, in step (a), the amount ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, maleic anhydride and tetrahydrofuran is 50-60 g: 20-30 g: 40-60 mL; the reaction temperature is 50-70° C., and the reaction time is 10-15 h; In step (b), the reaction temperature is 70-90° C., the reaction time is 0.5-2 h; the amount ratio of triethylenetetramine to tetrahydrofuran is 5-15 g:40-60 mL; In step (c), the reaction temperature is 90-110° C., the reaction time is 1-3 h; the amount ratio of ethylenediamine to tetrahydrofuran is 20-30 g: 40-60 mL; In step (d), the usage ratio of water to tetrahydrofuran is 100-120 g:40-60 mL.
5. The preparation method according to any one of claims 1 to 4, characterized in that: In the step S3, the mass ratio of the nano-hybrid DE@TA to the S-DIHP material is 10-20:
100.
6. The preparation method according to claim 5, characterized in that: In the step S3, in the process of preparing the nano hybrid DE@TA, in step (1), the mass ratio of 9,10-dihydro-9-oxa-10-phosphaphenanthrene-10-oxide, coupling agent KH560 and toluene is 5-15:5-15:20-40; the reaction temperature is 90-110° C., and the reaction time is 4-8 hours; In step (2), the reaction temperature is 50-70° C., the reaction time is 4-8 hours; the mass ratio of ethanol, water and toluene is 20-30:1-5:20-40; In step (3), the mass ratio of polysiloxane, tannic acid and water is 1-5:1-5:40-60.
7. The boiling water resistant flame retardant starch-based wood adhesive prepared by the preparation method according to any one of claims 1 to 6.
8. Use of the boiling water resistant flame retardant starch-based wood adhesive according to claim 7 in the preparation of laminated plywood, characterized in that: The following steps are involved: The poplar veneer is dried, glued, assembled and hot-pressed in sequence to obtain a laminated plywood; In the gluing process, the amount of the boiling water resistant flame retardant starch-based wood adhesive on the poplar veneer is 200-400 g / m 2 ; The temperature of the hot pressing is 170-190° C., the pressure of the hot pressing is 0.5-2 MPa, and the time of the hot pressing is 3-10 min.
9. The use according to claim 8, characterized in that: After the drying, the moisture content of the poplar veneer is ≤8%.
Citation Information
Patent Citations
Biomass starch adhesive as well as preparation method and application thereof
CN117402571A
Tannic acid-based flame retardant containing phosphorus, silicon and nitrogen as well as preparation method and application of tannic acid-based flame retardant
CN118063536A